Different Behavior of Enteric Bacteria and Viruses in Clay and Sandy Soils after Biofertilization with Swine Digestate - Fongaro, Gislaine; García-González, María C.; Hernández, Marta; Kunz, Airton; Barardi, Célia R. M.; Rodríguez-Lázaro, David (Frontiers in Microbiology, 2017)
Enteric pathogens from biofertilizer can accumulate in the soil, subsequently contaminating water and crops. We evaluated the survival, percolation and leaching of model enteric pathogens in clay and sandy soils after biofertilization with swine digestate: PhiX-174, mengovirus (vMC0), S. enterica Typhimurium and Escherichia coli O157:H7 were used as biomarkers. The survival of vMC0 and PhiX-174 in clay soil was significantly lower than in sandy soil (iT90 values of 10.520 0.600 vs 21.270 1.100 and 12.040 0.010 vs 43.470 1.300, respectively) and PhiX-174 showed faster percolation and leaching in sandy soil than clay soil (iT90 values of 0.46 and 2.43, respectively). S. enterica Typhimurium was percolated and inactivated more slowly than E. coli O157:H7 (iT90 values of 9.340 0.200 vs 6.620 0.500 and 11.900 0.900 vs 10.750 0.900 in clay and sandy soils, respectively), such that E. coli O157:H7 was transferred more quickly to the deeper layers of both soils evaluated (percolation). Our findings suggest that E. coli O157:H7 may serve as a useful microbial biomarker of depth contamination and leaching in clay and sandy soil and that bacteriophage could be used as an indicator of enteric pathogen persistence. Our study contributes to development of predictive models for enteric pathogen behaviour in soils, and for potential water and food contamination associated with biofertilization, useful for risk management and mitigation in swine digestate recycling.